Romantic rascals - Finger, Charles Joseph, 1869-1941. (New York, R.M. McBride & Company, 1927)
Luigi [!] di Barthema.--Three splendid scoundrels: "Count" St. Germain, "Count" Cagliostro, Jeanne de Valois --The Tichborne claimant.--John Cottingham.--A pair of kings: Ali Pasha ;of Albania; Jorgen Jorgenson, protector of Iceland.--King Cambiaso of Patagonia and Terra del Fuego. Mode of access: Internet.